Pengaruh ROA dan ROE terhadap Kinerja Keuangan Perusahaan Sektor Hotel, Rekreasi dan Pariwisata - Hana’a Afifah; Deni Ramdani (Pusat Riset dan Inovasi Nasional, 2023)
In business, companies compete with each other in their own way to get big profits. Companies in the tourism, restaurant and recreation sector are companies that have an impact on the company's financial performance and profitability. The variables used in this study are profitability ratios in the form of Return on Assets (ROA) and Return on Equity (ROE) as well as financial performance. This research uses quantitative methods. The sample used is 10 tourism, hotel and restaurant sector companies. The results of this study show that the ROA and ROE variables have a partial and significant effect on financial performance variables. The R-Square result is 0.3048 so that it can be interpreted that 30.48% of the ROA and ROE variables can explain the Financial Performance variable and the remaining 69.52% can be explained by other variables outside the research.